May probable cause of hypertension in hypertensive disorders of pregnancy be over expressing tyramine depending deterioration of microbiota composition - Aydin, Suleyman; Ustebay, Sefer; Baykus, Yakup; Deniz, Rulin (Elsevier, 2019)
[Abstract Not Available]
Keywords: Microbiota; Hypertension; Pre-eclampsia; Catecholamine; Tyramine